Environmental perception of the Policeman Squad of state of Sergipe on Environmental Agenda in Public Administration - Costa, Cristiano Cunha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work aimed to study the perception of the military police on the implementation of the environmental agenda in public administration in Environmental Platoon as a way to understand the relationship of the same with the quality of life and the adoption of sustainable practices within the workplace. For this, there was the collection of information through a semi-structured questionnaire with open and closed questions, can know the profile of the military, work environment, generated solid waste and rational use material. It used the statisticalprogram SPSS for Windows 1.0. It was observed that the majority of respondents did not know theA3P program, but said they would adopt the program in their environment d etrabalho and there are a variety of solid waste, but there is no separate collection. It is necessary toseek solutions to problems identified through the development and implementation of environmental actions. So it is necessary an effective environmental policy within the institution.